'Tackling' race inequality in school leadership: Positive actions in BAME teacher progression – evidence from three English schools. (November 2020) - Miller, Paul Washington
The career progression of teachers of black, Asian and minority ethnic heritage is a matter of much debate and research. Over the past decade, a body of research has confirmed that race discrimination/race inequality is a factor in the progression of teachers of black, Asian and minority ethnic heritage in England. Although it has been argued that 'Britain is not a racist nation', it nonetheless has, as described by Phillips in 2016, a '…deep sensitivity to…ethnic and cultural difference'. According to Miller, this sensitivity remains at the heart of a 'deep-rooted and continuing struggle among black, Asian and minority ethnic teachers and academics for equality and mutual recognition'. Drawing on Miller's 2016 typology of educational institutions: engaged, experimenting, initiated and uninitiated, this paper presents evidence from three English headteachers of Multi-Academy Trusts who devise, implement and embed positive actions in the recruitment, development, retention and progression of staff of black, Asian and minority ethnic heritage. The objective of this study was to examine the work of school leaders/institutions in taking steps to improve black, Asian and minority ethnic teacher progression in England, by identifying and highlighting 'what works', and how. Furthermore, by treating each school/leader as a unique 'case', this paper shows their motivation (personal and professional), experiences of 'race', school contexts and the type/s of leadership required and used in these institutional contexts to change attitudes, cultures and behaviours.